Progressive Law Analysis of Injustice in Asset Value Requirements for Construction Services - Misno Misno; Ahmad Ahmad; Istiqomah Istiqomah; Aris Gumilar (Universitas Muhammadiyah Tangerang, 2024)
The Minister of Public Works and Housing Regulation No. 8 of 2022 establishes an asset value requirement of IDR 5 billion for M2 qualification in the installation sector, consequently marginalizing 88% of small-scale construction service enterprises. This research employs qualitative methodologies incorporating juridical-normative and juridical-empirical approaches to analyze the regulatory injustice through the lens of Satjipto Rahardjo's Progressive Law Theory. Data were collected through in-depth interviews with 25 respondents representing diverse stakeholder categories. The findings demonstrate that asset value requirements lack adequate philosophical, juridical, and sociological foundations for the installation sector, which functions as a knowledge intensive industry. The regulatory implementation engenders distributive, procedural, and interactional injustice, contradicting the fundamental principle of